A Lightweight Encryption Method for Privacy Protection in Surveillance Videos - Xing Zhang; Seung-Hyun Seo; Changda Wang (IEEE Access, 2018)
Privacy protection of surveillance videos is an important issue because of the pervasiveness of surveillance cameras. Region of interest (RoI) privacy protection prefers encrypting limited privacy-sensitive areas to encrypting the entire video because of the resource-tightened Internet of Things devices. However, many cryptographic technologies now applied in privacy protection, e.g., AES and RSA, are not efficient to meet the real-time requirement for surveillance videos. A lightweight encryption approach is then devised based on layered cellular automata (LCA). Using our approach, the extracted RoIs are fed into the initial state of an 8-layer cellular automata, which is driven by the randomly selected rules for the LCA's state transitions. As a result, all RoIs are encrypted independently and synchronously. The encrypted RoIs are stored at the camera side and can be used by authenticated users through an on-demand manner. The surveillance video without RoIs can be watched in real-time by any user online. Theoretical analyses and experimental results show that our approach is both efficient and effective.